Phoenixin-20 suppresses lipopolysaccharide-induced inflammation in dental pulp cells. (25th February 2020) - Sun, Guohui; Ren, Qihui; Bai, Li; Zhang, Lin
Abstract: Pulpal infection is one of the most common causes of dental emergency admission. Tooth pain due to infection caused by gram-negative bacteria is the main manifestation of this sort of dental problem. The GPR173 signaling pathway is a highly conserved G-protein-coupled receptor that mediates neurological and reproductive function. In this study, we found that GPR173 was fairly expressed in isolated human dental pulp cells, and its expression was reduced in response to pro-inflammatory lipopolysaccharide (LPS) treatment. The activation of GPR173 by its ligand Phoenixin-20 reduced LPS-induced cytotoxicity, as revealed by a reduction in the release of LDH. Additionally, Phoenixin-20 suppressed LPS-induced release of pro-inflammatory cytokines and inflammatory mediators, including IL-6, MCP-1, VCAM-1, and ICAM-1, as well as MMP-2 and MMP-9. Mechanistically, we showed the suppressive action of Phoenixin-20 on LPS-induced activation of TLR-4 and Myd88 as well as the activation of the NF-κB pathway. Collectively, our study demonstrates that the GPR173 signaling pathway is an important mediator of LPS-induced inflammation, and the activation of GPR173 by its natural ligand Phoenixin-20 exhibits robust anti-inflammatory effects in dental pulp cells, suggesting that GPR173 is an interesting target molecule in the development of pulp cell-based therapies. Highlights: LPS reduced the expression of GPR173 in human dental pulp cells (hDPCs). Phoenixin-20 reduced LPS- induced release of LDH in hDPCs. Phoenixin-20 reduced LPS- induced IL-6, MCP-1, VCAM-1, ICAM-1, MMP-2, and MMP-9. Phoenixin-20 abolished LPS- induced activation of TLR4/Myd-88/NF-kB in hDPCs.